2022
DOI: 10.1186/s12941-022-00509-3
|View full text |Cite
|
Sign up to set email alerts
|

Heteroresistance to clarithromycin and metronidazole in patients with a Helicobacter pylori infection: a systematic review and meta-analysis

Abstract: Background Antimicrobial resistance of H. pylori can lead to treatment failure. Importantly, several studies have reported on heteroresistance, i.e. the presence of resistant and susceptible H. pylori populations in the same sample and/or a difference in the susceptibility patterns between biopsy samples. This meta-analysis aims to provide comprehensive data on the prevalence of metronidazole and clarithromycin heteroresistance and the approaches to their detection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…26 Heteroresistance for H. pylori was first described in different studies in the 90s when a Belgian microbiologist decided to seed the biopsy samples obtained from the antrum and from the corpus on separate plates. 27,28 This discovery could help to understand better the failure to eradicate H. pylori. However, the emergence of heteroresistance in H. pylori strains has never been discussed in published guidelines, 9 and most laboratories still seed the biopsies on the same plate to lower the cost (in the last pediatric guideline, it is even recommended to place different samples into the same transport jar).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Heteroresistance for H. pylori was first described in different studies in the 90s when a Belgian microbiologist decided to seed the biopsy samples obtained from the antrum and from the corpus on separate plates. 27,28 This discovery could help to understand better the failure to eradicate H. pylori. However, the emergence of heteroresistance in H. pylori strains has never been discussed in published guidelines, 9 and most laboratories still seed the biopsies on the same plate to lower the cost (in the last pediatric guideline, it is even recommended to place different samples into the same transport jar).…”
Section: Discussionmentioning
confidence: 99%
“…Heteroresistance for H. pylori was first described in different studies in the 90s when a Belgian microbiologist decided to seed the biopsy samples obtained from the antrum and from the corpus on separate plates 27,28 . This discovery could help to understand better the failure to eradicate H. pylori .…”
Section: Discussionmentioning
confidence: 99%
“…A further issue concerning rising resistance rates is the presence of heteroresistance of H. pylori , where a heterogeneous population of H. pylori may exist within an individual, with one or several subpopulations exhibiting increased levels of antibiotic resistance compared with the main population 23 . Recent reviews have demonstrated the presence of heteroresistance to clarithromycin and/or metronidazole in approximately 7% and 14% of H. pylori –positive isolates 24 . In our study, 81 isolates were from patients who underwent repeated successful culture.…”
Section: Discussionmentioning
confidence: 99%
“…23 Recent reviews have demonstrated the presence of heteroresistance to clarithromycin and/or metronidazole in approximately 7% and 14% of H. pylori-positive isolates. 24 In our study, 81 isolates were from patients who underwent repeated successful culture. In these cases, prior culture-directed therapy was not successful at eradicating H. pylori, and the presence of heteroresistance is likely to be the cause.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, heteroresistance of H. pylori may also affect the efficacy of TT for the reason that both susceptible and resistant strains can be simultaneously present in different sites of a single stomach and that antibiotic susceptibility may change during treatment 59,60 . It was reported that heteroresistance to clarithromycin, levofloxacin, and metronidazole is not rare in H. pylori 61,62 …”
Section: Discussionmentioning
confidence: 99%